Does environmentally biased technological progress reduce air pollution emissions? empirical analysis based on spatial model and PSTR model - Meng, Yuxin; Liu, Lu; Ran, Qiying (Frontiers in Environmental Science, 2022)
Environmental policies and environmentally biased technological advances have important theoretical value and practical significance for air pollution reduction and green economic development in China. The article is based on panel data for 270 cities in China from 2007 to 2020. Using a spatial Durbin model, the direct, spillover and moderating effects of biased technological progress on 'local-neighbourhood' urban air pollution are examined empirically. On this basis, the threshold model is used to further explore the non-linear effects of different types of environmental regulations. The study found that: (1) There is a significant positive spatial correlation between both air pollution and biased technological progress in China. Biased technological progress significantly suppresses air pollution, with significant negative spatial spillover effects, and the conclusions remain robust after a series of robustness tests. (2) Different types of environmental regulations reinforce the dampening effect of biased technological progress on air pollution. However, formal environmental regulation only reinforces the dampening effect of biased technological progress on air pollution in the local cities but promotes air pollution in neighbouring cities. (3) There is a significant threshold effect of environmental regulation on the impact of biased technological progress on air pollution. When the level of environmental regulation reaches a certain threshold, biased technological progress has a dampening effect on air pollution. (4) The more eastern the city, the larger the city and the non-resource-based cities, the more significant the air pollution suppression effect of biased technological advances. Based on this, this study points out that governments at all levels should pay attention to the spatial spillover effect of technological progress bias on air pollution, deepen the construction of joint prevention and control mechanisms for regional air pollution control; establish multiple environmental regulation policies, formulate and implement environmental regulation policies according to local conditions and local technological progress bias; and formulate targeted environmental regulation policies and technological innovation policies according to the characteristics of different cities. It is an important theoretical reference to help China to fight the battle against air pollution in-depth and to promote further improvement of ecological and environmental quality.